PENGARUH METODE DEMONSTRASI PADA MINAT BELAJAR IPA SISWA KELAS IV DI MI DARURROHMAN KERTANEGARA HAURGEULIS - Annisa Fitria Nurjanah; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
Learning Natural Sciences (IPA) at the basic level should be interesting learning and arouse students' interest in learning. Thus, it is necessary for educators, learning methods, media, and an appropriate environment to arouse students' interest in learning science, especially in class IV students of MI Darurrahman Haurgeulis. This study aims to determine the effect of the demonstration method and whether there is a positive influence on the interest in learning science at elementary level students. This study uses the semi experiment method (Quasi Experimental Method) with the design model of the time series experiment. The instrument used is a questionnaire using the scale Guttman. The sample used in this study were fourth grade students at MI Darurrohman, totaling 16 people. The results showed that the demonstration method had a very high effect on students' interest in learning science by 83.1% with an interval of 80%-100%. These results prove that there is a significant positive influence of the demonstration method on the interests of learning IPA grade IV students at MI Darurrohman Kertanegara Haurgeulis.